Antibacterial activity and the physicochemical characteristics of plasma activated water on tomato surfaces. (September 2021) - Hou, Chih-Yao; Lai, Yu-Ching; Hsiao, Chun-Ping; Chen, Song-Yue; Liu, Chih-Tung; Wu, Jong-Shinn; Lin, Chia-Min
Abstract: A new technique, plasma activated water (PAW), was used to inactivate bacteria on the tomato surface. The PAW was generated at 60 Watts (W) for 20 min using air flow rates at 6 or 10 standard liter per min (slm) with 1 or 2 plasma jet(s). Tomatoes inoculated with Salmonella Typhimurium, Escherichia coli, or Listeria monocytogenes were treated by the PAW for 30, 60, 90, 120, 150, 180 or 210 s. Significantly higher reductions ( p < 0.05) of bacterial populations were obtained with 2 plasma jets. More than 5 log reductions of S . Typhimurium, E. coli, and L . monocytogenes were obtained when treated with 2 acting plasma jets for 30, 180, and 210 s, respectively. When treatment time increased, lower values of pH and higher values of oxidative reduction potential, nitrite, nitrate, ozone, and peroxide were obtained. An analysis of the electron paramagnetic resonance confirmed the generation of reactive oxygen species in PAW. This study showed that PAW was effective against bacteria on tomato surfaces and offered evidences for the antibacterial mechanism of PAW. Highlights: Reducing S. Typhimurium, E. coli, and L. monocytogenes on tomato. S. Typhimurium and L . monocytogenes was the most susceptible and resistant, respectively. The concentrations of NO2 −, NO3 −, O3, and H2 O2 were correlated with the antibacterial efficacy. The generation of ROS was confirmed.